Advances in Image and Graphics Technologies Chinese Conference, IGTA 2014, Beijing, China, June 19-20, 2014. Proceedings - Tan, Tieniu; Ruan, Qiuqi; Wang, Shengjin; Ma, Huimin; Huang, Kaiqi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the referred proceedings of the 8th China Conference on Image and Graphics Technologies and Applications, IGTA 2014, held in Beijing, China, in June 2014. The 39 papers presented were carefully reviewed and selected from 110 submissions. They cover various aspects of research in image processing and graphics and related topics, including object detection, pattern recognition, object tracking, classification, image segmentation, reconstruction, etc.
Image processing and graphics and related topics -- Object detection -- Pattern recognition -- Object tracking -- Classification -- Image segmentation -- Reconstruction.
Keywords: Computer science; Coding theory; Computers; Artificial intelligence; Computer simulation; Computer graphics; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Artificial Intelligence (incl. Robotics).; Models and Principles; Computation by Abstract Devices; Coding and Information Theory; Simulation and Modeling; Electronic books